The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00436-004-1227-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural infestation of the chewing lice (Werneckiella equi) on horses and treatment with imidacloprid and phoxim

Abstract: Infestation with the chewing louse (Werneckiella (Damalinia) equi) can be found on horses world-wide. Louse infestations, including clinical signs of louse-derived dermatitis, are known from Icelandic horses. A clinical field investigation was conducted in Iceland using horses with natural louse infestations to evaluate the efficacy of imidacloprid in a 10% solution in comparison with phoxim in a 0.05% solution. A total of 27 horses received a single imidacloprid treatment using 16 ml of the 10% solution along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…Further variables for a topical-applied compound are the behavioural factors of the animal species. For the treat- (Mencke et al 2004) demonstrated the efficacy of imidacloprid against lice. A dose of 16 ml of the 10% imidacloprid solution was effective to clear an existing lice infestation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Further variables for a topical-applied compound are the behavioural factors of the animal species. For the treat- (Mencke et al 2004) demonstrated the efficacy of imidacloprid against lice. A dose of 16 ml of the 10% imidacloprid solution was effective to clear an existing lice infestation.…”
Section: Discussionmentioning
confidence: 98%
“…Housing of horses was described previously by Mencke et al (2004). The 93 horses included into this study belonged to a total of 158 horses out of 15 individual stables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, under in vivo conditions we found that the anthelmintic effect was only moderate. Meyer-Kuhling et al (2007) reported that just a single administration of phoxim killed 99.1% of red mites, while previous studies have reported that the majority of lice and fleas treated with phoxim were killed at the end of treatment (Larsen et al, 2005;Mencke et al, 2004). Hence, the anthelmintic efficacy of phoxim on Dactylogyrus appeared far less than its effects on other genera of ectoparasites.…”
Section: Discussionmentioning
confidence: 95%